2015
DOI: 10.1002/bem.21890
|View full text |Cite
|
Sign up to set email alerts
|

Reduced growth of soybean seedlings after exposure to weak microwave radiation from GSM 900 mobile phone and base station

Abstract: The aim of this work was to study possible effects of environmental radiation pollution on plants. The association between cellular telephone (short duration, higher amplitude) and base station (long duration, very low amplitude) radiation exposure and the growth rate of soybean (Glycine max) seedlings was investigated. Soybean seedlings, pre-grown for 4 days, were exposed in a gigahertz transverse electromagnetic cell for 2 h to global system for mobile communication (GSM) mobile phone pulsed radiation or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…Furthermore, metabolic mutants are easily available for several species and constitute invaluable tools to understand the way the EMF signal is transduced [ 6 ]. Indeed, several reports have pointed out that plants actually perceive HF-EMF of even small amplitudes and transduce them into molecular responses and/or alterations of their developmental scheme [ 3 9 ]. The way that HF-EMF interact with plants remains essentially unanswered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, metabolic mutants are easily available for several species and constitute invaluable tools to understand the way the EMF signal is transduced [ 6 ]. Indeed, several reports have pointed out that plants actually perceive HF-EMF of even small amplitudes and transduce them into molecular responses and/or alterations of their developmental scheme [ 3 9 ]. The way that HF-EMF interact with plants remains essentially unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, EMF exposure alters the activity of several enzymes, including those of reactive oxygen species (ROS) metabolism [ 7 ], a well-known marker of plant responses to various kinds of environmental factors. EMF exposure also evokes the expression of specific genes previously implicated in plant responses to wounding [ 5 , 8 ] and modifies the development of plants [ 9 ]. Furthermore, these responses are systemic insofar as exposure of only a small region of a plant results in almost immediate molecular responses throughout the plant [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[50] Halgamuge et al also reported the reduction of epicotyl and hypocotyl growth in soybean seeds after exposure to weak microwave radiation. [51] HF-EMF radiation is noninjurious, but its long-term impact on metabolic changes in plants remains unclear. [52] Ozlem-Caliskan et al investigated the effect of EMF on parasite growth and reported that EMF exposure might decrease in the number of parasites, and EMF has some effect on the growth of parasites which needs to be investigated further.…”
Section: Sleepmentioning
confidence: 99%
“…This paper used raw-data of plant exposure from our previous review study [1] (extracted data set from 45 peer-reviewed scientific publications (1996-2016) with 169 experimental observations carried out in the scientific literature, e.g. [23] and performed prediction extracting high levels of knowledge from raw data using different classification algorithms and performance evaluation methods. Moreover, we used these data sets for clustering algorithms.…”
Section: B Data Collectionmentioning
confidence: 99%